Pengembangan Media E-Comel (Komik Melayu Digital) Untuk Meningkatkan Perilaku Moral Anak Usia 5-6 Tahun - Nadia Ramona; Rita Kurnia; Zulkifli N (Innovative: Journal Of Social Science Research, 2023)
This study aims to describe the process and learning outcomes through the application of the use of E-Comel media (digital Malay comics) which can improve the moral behavior of children aged 5-6 years. The type of research used is research and development (Research and Development). The steps taken are potential and problems, data/information collection, product design, product design validation, design revision, product manufacture, and product trials. Data collection techniques by observation, distributing questionnaires, and analysis of documentation. The instrument used was a questionnaire for validating E-COMEL media from media experts, material experts, linguists and educators. The data analysis technique used is a quantitative descriptive analysis technique by using the experimental method. In the study, the validation of material experts was obtained for 97.92% "very decent", validated media experts for97.00% “very feasible”, linguist validation87.50% “very decent” educator validation results obtained a percentage of 94.05% "very feasible". From the results of the study it was concluded that the E-COMEL media (Digital Malay Comics) namely the average score of moral behavior before treatment (pretest) was 50.48% and in the posttest was 84.76%. The results of N-Gain obtained a score of 63.46%. From the results of the study it was concluded that E-COMEL media is suitable for use as a learning medium in the moral behavior of children aged 5-6 years at Permata Bunda Kindergarten, Peranap District.